STUDI KERJA PROTEKSI RELAI OCR DAN GFR PADA PENYULANG ULUWATU SETELAH REKONFIGURASI - Santosa, Galih Budi; Dyana Arjana, I Gede; Arta Wijaya, I Wayan (Jurnal SPEKTRUM; Vol 8 No 3 (2021): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2021.v08.i03.p14, 2021)
PT. PLN (Persero) South Bali Area built the Pecatu GIS to level the load, improve service and reliability of the electricity distribution system. The transfer of electrical loads to the Pecatu GIS changes the configuration of the Pecatu feeder to the Uluwatu feeder and the Labuan Sait feeder. Changes in load current and network impedance have an impact on short-circuit fault currents. The calculation of short-circuit fault current becomes the basis for determining the working time of the OCR and GFR relays between the recloser and the feeder base PMT. The relay working time based of the PLN regulation setting protection at 0,1 seconds to eliminate fault currents and IEC 60255 standard take 0,3 seconds to eliminate fault currents. The results of the study showed that the time value of PLN's regulation Tms was 0,076 SI and 0,033 SI. The results of the calculation of (Tms) standard IEC 60255 obtained time (Tms) 0,23 SI and 0,09 SI. The simulation results of the PLN regulation relay settings and IEC 60255 work well with a grading time value of 0,2 – 0,4 seconds.